2004
DOI: 10.1016/j.febslet.2004.03.090
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Klotho protein in sera and CSF: implication for post‐translational cleavage in release of Klotho protein from cell membrane

Abstract: Klotho mutant mice exhibit a set of phenotypes resembling human ageing. Although the function of Klotho remains unclear, mediation of its pleiotropic functions by putative humoral factor(s) has been presumed. Newly established antibodies against Klotho allowed the detection of secreted Klotho, a candidate for the putative humoral factor, in sera and cerebrospinal fluid. Surprisingly the secreted Klotho was 130 kDa, in contrast to the 70 kDa predicted form from klotho gene transcripts. The secreted as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
233
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(247 citation statements)
references
References 11 publications
7
233
0
2
Order By: Relevance
“…Moreover the previous findings also agree with Derakhshanfar et al (2007) provides evidence that pre-treatment of vitamin E can prevent both the functional and histological renal changes in nephtotoxicity. Similar results found by Koh et al (2001) and Imura et al (2004) reported severely reduced production of klotho in urine and kidneys (messenger RNA and protein) by Western blot of patients with acute renal failure and klotho levels have been shown to correlate negatively with plasma creatinine levels. Also the previous results come in harmony with the results obtained by El-Far et al (2005) found the presence of significant negative correlation between GPx activity and serum creatinine level.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover the previous findings also agree with Derakhshanfar et al (2007) provides evidence that pre-treatment of vitamin E can prevent both the functional and histological renal changes in nephtotoxicity. Similar results found by Koh et al (2001) and Imura et al (2004) reported severely reduced production of klotho in urine and kidneys (messenger RNA and protein) by Western blot of patients with acute renal failure and klotho levels have been shown to correlate negatively with plasma creatinine levels. Also the previous results come in harmony with the results obtained by El-Far et al (2005) found the presence of significant negative correlation between GPx activity and serum creatinine level.…”
Section: Discussionsupporting
confidence: 75%
“…Admittedly, we cannot provide our own experimental data to support this favoured hypothesis. aKL (130 kDa) appears to result from proteolytic ectodomain clipping (10). Two members of the ' A Disintegrin and Metalloproteinase' (ADAM) family, ADAM10 and ADAM17, have been suggested as the responsible enzymes (9), and the activity of secretases (25,26) shedding the ectodomain from the integral membrane Klotho may be increased in acromegaly, either directly by GH or indirectly by factors or a proteolytic activity induced by GH.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms leading to soluble aKL excess in the serum in active acromegaly remain unclear. Soluble aKL could arise either from a distinct transcript (24) or from ectodomain shedding of membrane Klotho (9,10,25). It remains unclear whether in acromegalics membraneassociated Klotho (mainly found in the kidneys) and soluble aKL (as detected in the serum) rise concurrently or whether elevated soluble aKL is unrelated or possibly inversely related to the abundance of plasma membrane Klotho in the kidneys -possibly resulting from enhanced enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It exists in 2 forms: The transmembrane and the soluble secreted form [163] . Klotho is detected as a soluble protein in body fluids including blood, CSF and urine [164] . The highest expression of Klotho is in the kidney and the brain [6] , but it is also expressed in parathyroid gland [165] and heart [166] with less abundance.…”
Section: Sharaf El Din Uaa Et Al Stop Chronic Kidney Disease Progrementioning
confidence: 99%